Optimalisasi Jaringan Menggunakan Teknik Load Balancing Metode Peer Connection Classifier (Studi Kasus: Dinas Perpustakaan Dan Kearsipan Provinsi Riau) - Satiarini, Astri; Safrianti, Ery; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Internet is a necessity for the current era. The number of requests for internet access cause long response time and overload. Especially in offices that provide public services such as the Department of Library and Archives in Riau Province. To keep service work at the Soeman HS Regional Library not interrupted, so it will give comfortable for visitors, network optimization will be carried out with Load Balancing Technique. Load Balancing will balance load traffic on two or more connection lines, so that traffic can run optimally. The method used is Peer Connection Classifier, whereas this method will divide load based on sources, destination addresses and port addresses. All internet requests from users will go to Router that has been configured with PCC method, so on the Router will set up the exit request from user through ISP 1 line or ISP 2 line to be able to go to internet connections. The test results show that the equal distribution of outgoing access to ISP 1 and ISP 2 lines in a balanced manner, so there is no overload in any of ISP lines. The configuration will be applied in the Mikrotik Router using the Winbox application. Keywords : Load Balancing, Optimization, Peer Connection Classifier, Failover, ISP Lines.